FORENSIC EVALUATION OF SUDDEN DEATH AMONG YOUNG PEOPLE WITH DISPLASIA OF CONNECTING TISSUE - Yu. I. Pigolkin; M. A. Shilova; I. V. Globa (Сеченовский вестник, 2018)
Sudden death among young people attracts attention of doctors of different specialties - cardiologists, neurologists, pediatricians, doctors of sport medicine. Determination of the cause of death in such cases is legally performed only through forensic medical examination. As a rule, the deceased fall under the category of young, able odied, of reproductively and economically promising age - schoolchildren, students, cadets of higher military institutions, sportsmen or persons engaged in sports activities. The circumstances of the onset of death in young people often include physical activities of different nature. The onset of death occurs against in allegedly healthy people, without any pathology diagnosed intra vitam. However, forensic medical examination always reveals either latent or not diagnosed in time pathology of the cardiovascular system. It is established that among all young people who died suddenly, there are signs of connective tissue dysplasia that are revealed both in external and internal examination of the corpse. The article describes the main clinical and morphological manifestations of connective tissue dysplasia, the pathology of various organs and systems, as well as the causes of sudden death of young people with this pathology.